2020
DOI: 10.1177/0963721420903015
|View full text |Cite
|
Sign up to set email alerts
|

Putting Effort Into Infant Cognition

Abstract: Working memory allows people to manipulate information in support of ongoing tasks and provides a work space for cognitive processes such as learning, reasoning, and decision making. How well working memory works depends, in part, on effort. Someone who pays attention at the right time and place will have better memory and improved performance on memory tasks. In adult cognitive research, participants’ devotion of maximal task-focused effort is often taken for granted, but in infant studies, researchers cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Therefore, the uncertainty resulting from a surprising event might increase the amount of cognitive effort deployed to explore and analyze the unexpected event outcome, which in turn might result in deeper encoding and better memory for the surprising item. In accordance with the idea that pupil size is a reliable measure of cognitive effort (Granholm et al, 1997; Hess & Polt, 1964), increased pupil dilation during encoding has been associated with enhanced memory performance in both adults (Goldinger et al, 2009; Papesh et al, 2012) and infants (Cheng et al, 2019; Káldy & Blaser, 2020).…”
Section: Introductionmentioning
confidence: 57%
“…Therefore, the uncertainty resulting from a surprising event might increase the amount of cognitive effort deployed to explore and analyze the unexpected event outcome, which in turn might result in deeper encoding and better memory for the surprising item. In accordance with the idea that pupil size is a reliable measure of cognitive effort (Granholm et al, 1997; Hess & Polt, 1964), increased pupil dilation during encoding has been associated with enhanced memory performance in both adults (Goldinger et al, 2009; Papesh et al, 2012) and infants (Cheng et al, 2019; Káldy & Blaser, 2020).…”
Section: Introductionmentioning
confidence: 57%
“…While we chose pupil dilation as a measure because of its relationship with conflict, it is important to note that we cannot be sure that pupil dilation itself reflects the process of perceiving or experiencing conflict. Pupil dilation has also been associated with both violation of expectation (Jackson & Sirois, 2009) and effort (Kaldy & Blaser, 2020) and it is not clear whether these processes are independent (Laeng et al, 2012). As we find this difference during the anticipatory time window, an alternative possibility is that it reflects the prediction process itself.…”
Section: Discussionmentioning
confidence: 99%
“…Change in pupil diameter has been used as a marker of cognitive effort in both adults and infants (Hess & Polt, 1960;Kahneman & Beatty, 1966;Kaldy & Blaser, 2020).…”
Section: Emerging Self-representation Presents a Challenge For Perspective Tracking In Infancymentioning
confidence: 99%
“…We have also shown that pupil dilation alone can predict performance and looking time is not needed as an additional predictor. In sum, babies' effortful cognitive circuits work very similarly to adults', and pupillometry can also provide a methodological solution to the 'blank stare' problem (Kaldy & Blaser, 2020).…”
Section: Are Children's Long-term Memories Always Worsementioning
confidence: 99%